Factors Influencing Participation in COVID-19 Clinical Trials: A Multi-National Study - Abdelhafiz, Ahmed Samir; Abd ElHafeez, Samar; Khalil, Mohammad Adnan; Shahrouri, Manal; Alosaimi, Bandar; Salem, Raneem O.; Alorabi, Mohamed; Abdelgawad, Fatma; Ahram, Mamoun (Frontiers in Medicine, 2021)
In 2020, the World Health Organization has characterized COVID-19, a disease caused by infection with the SARS-CoV-2 virus, as a pandemic. Although a few vaccines and drugs have been approved to, respectively, prevent or treat the disease, several clinical trials are still ongoing to test new vaccines or drugs to mitigate the burden of the pandemic. . Few studies have shown the role of host genetics in disease prognosis and drug response highlighting the importance of diverse participation in COVID-19 clinical trials. The goal of this study is to assess public attitudes in Egypt, Saudi Arabia, and Jordan towards participating in COVID-19 clinical trials and to identify the factors that may influence their attitude. An online questionnaire was developed and distributed among the target group through social media platforms. The number of responses was 1576. Three quarters (74.9%) of participants heard about clinical trials before, 57.6% of them had a positive attitude towards participation in COVID-19 clinical trials. The conduct of clinical trials in accordance with the scientific, research, and ethical guidelines was a strong predictor of willingness to participate in clinical trials. Other positive factors also included protection of family from COVID-19 and contributing to the return to normal community life as well as receiving additional healthcare benefit was the fourth significant predictor. On the other hand, the thought that clinical trials can have a negative impact on the health of participants strongly predicted the unwillingness of individuals to participate in such trials. This was followed by having limited information about the novel coronavirus and COVID-19 and the lack of trust in physicians and hospitals. In general, Arab citizens are accepting the concept and have a positive attitude towards COVID-19 clinical trials. Increasing awareness of COVID-19 and clinical trials, enforcing the concept of altruism, and placing clear policies in conducting clinical trials are needed to increase participation in clinical trials among Arabs.